Does Risk Attitude Increase the Effect of Financial Literacy on Access to Finance? - Addo, Selma Dzifa; Asantey, Joseph; Awadzie, David Mensah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
The paper aimed to examine the moderating impact risk attitude has on the link between financial literacy and access to funding for SMEs. Respondents included SMEs in Accra via standardized questionnaires. 396 accurate responses were analyzed utilizing PLS-SEM. Findings showed an important beneficial correlation between knowledge of finances and credit accessibility. The relationship between risk-taking behavior and financial access also proved significant. Additionally, the study discovered that the connection between financial competence and financial access is significantly moderated by risk-taking tendency. The results support the knowledge base view theory, according to which financial literacy is a unique strategic asset that firms can exploit to gain an advantage over rivals. Additionally, it was established that risk-averse owners/managers are more likely to miss out on possibilities to build wealth, which opens up access to credit or even poses the willpower to access debt finance